PENGARUH PENERAPAN SAMSAT KELILING, SAMSAT DRIVE THRU, DAN e-SAMSAT TERHADAP KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR DI KOTA MATARAM - Pratama, Andrian; Nurabiah, Nurabiah (Universitas Dharmawangsa, 2025)
This study aims to determine the effect of mobile samsat, drive thru samsat, and e-samsat on motor vehicle taxpayer compliance in Mataram City. This study uses an associative quantitative approach. The sample withdrawal in this study used purposive sampling. Based on the Slovin formula, the minimum sample processed in this study was 100 taxpayers registered at the joint service office of Samsat in Mataram City. Data was obtained by distributing questionnaires via Google Forms. The data was processed using SmartPLS 4.0. The results showed that the mobile samsat variable had a positive and significant effect on the compliance of motor vehicle taxpayers in Mataram City. Furthermore, the drive thru samsat variable does not affect motor vehicle taxpayers compliance in Mataram City. Then, the e-samsat variable does not affect the compliance of motor vehicle taxpayers in Mataram City. The results of this study can provide implications in understanding the effectiveness of each service because this study identifies which services are most effective in increasing taxpayer compliance.